Impact of basic life-support training on the attitudes of health-care workers toward cardiopulmonary resuscitation and defibrillation - Mostafa A. Abolfotouh; Manal A. Alnasser; Alamin N. Berhanu; Deema A. Al-Turaif; Abdulrhman I. Alfayez (BMC, 2017)
Abstract Background Cardiopulmonary resuscitation (CPR) increases the probability of survival of a person with cardiac arrest. Repeating training helps staff retain knowledge in CPR and in use of automated external defibrillators (AEDs). Retention of knowledge and skills during and after training in CPR is difficult and requires systematic training with appropriate methodology. The aim of this study was to determine the effect of basic life-support (BLS) training on the attitudes of health-care providers toward initiating CPR and on use of AEDs, and to investigate the factors that influence these attitudes. Methods A quasi-experimental study was conducted in two groups: health-care providers who had just attended a BLS-AED course (post-BLS group, n = 321), and those who had not (pre-BLS group, n = 421). All participants had previously received BLS training. Both groups were given a validated questionnaire to evaluate the status of life-support education and certification, attitudes toward use of CPR and AED and concerns regarding use of CPR and AED. Multiple linear regression analyses were applied to identify significant predictors of the attitude and concern scores. Results Overall positive attitudes were seen in 53.4% of pre-BLS respondents and 64.8% of post-BLS respondents (χ2 = 9.66, p = 0.002). Positive attitude was significantly predicted by the recent completion of BLS training (β = 5.15, p < 0.001), the number of previous BLS training courses (β = 2.10, p = 0.008) and previous exposure to cardiac-arrest cases (β = 3.44, p = 0.018), as well as by low concern scores, (β = −0.09, p < 0.001). Physicians had significantly lower concern scores than nurses (β = −10.45, p = 0.001). Concern scores decreased as the duration of work experience increased (t = 2.19, p = 0.029). Conclusions Repeated educational programs can improve attitudes toward CPR performance and the use of AEDs. Training that addressed the concerns of health-care workers could further improve these attitudes.